Crimes of the Internet - Schmalleger, Frank (Pearson, Prentice Hall)
Online predatory child victimization & exploitation -- Sexual addiction to the Internet: from curiosity to compulsion (Pittaro) -- Pedophilia, pornography, and stalking: analyzing child victimization Ion the Internet (Jaishankar/Halder/Ramdoss) -- Internet child sexual exploitation: offenses, offenders, and victims (Huang) -- Cyberbullying: a transnational perspective (Jaishankar & Shariff) -- Internet crimes: youth and children (Raghavan/Ranjan/Veddy) -- Emerging global crimes of the Internet -- Online pharmaceutical sales and challenges for law enforcement (Finley) -- Charges without borders: consumer credit card fraud in Ghana (Davison) -- Regulating cyberstalking (Basu/Jones) -- Internet gambling (Geiss/Brown/Pontell) -- Nature and distribution of phishing (Stroik/Huang) -- You can't cheat an honest man: Making ($$